ESTIMASI SUMBERDAYA PASIR BATU DENGAN METODE CROSS SECTION PADA DESA BIRU-BIRU KABUPATEN DELI SERDANG - Simanjuntak, Jefri; Halawa, Analiser; Lismawaty (LPPM ISTP, 2024)
Deli Serdang Regency is a Regency in North Sumatra Province which has natural resource potential in the form of non-metallic minerals and rocks. Stone sand (sirtu) comes from two parts, the large sized volcanic rock material and the fine sized consisting of clay and sand. Based on PP 96 of 2021, stone sand is included in the rock class. This research was conducted to determine resource estimates using the cross section method and the characteristics of rock sand in the research area. Data collection was carried out following the SNI 4726:2011 exploration concept, exploration stages include: review survey, inspection and general exploration of the surface of the mapping area. Based on the mapping results, the distribution of rock sand is not square (random), so using the trapezoidal method to assist in calculating the volume of rock sand in the calculation, we get an estimate of rock sand resources with an indicated resource classification, namely 641,812.5 m3 and the characteristics of rock sand with rock fragments which are thought to come from the mentar unit ( QTvm) and sand originating from the Keutapang (Tuk) formation. The sand-to-stone ratio in the southwestern deposition area is dominated by ±70% sand and ±30% stone, while in the northeastern deposition area it is dominated by ±80% rock and ±20% sand. The suggestion that the author can convey is the need to carry out subsurface mapping to determine the distribution and thickness of rock sand below the surface.